Encapsulation and self-superparasitism of Pseudapanteles dignus (Muesebeck) (Hymenoptera: Braconidae), a parasitoid of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Luna, María Gabriela (2016)
Endoparasitoids can be killed by host encapsulation, a cellular-mediated host immunological response against parasitism that involves hemocytes aggregation. As a counteracting strategy, many parasitoids can evade this host response through self-superparasitism. The objectives of this study were: 1) to describe the parasitoid Pseudapanteles dignus (Hymenoptera: Braconidae) early immature stages (egg and larva) encapsulation by the host Tuta absoluta (Lepidoptera: Gelechiidae), and 2) to determine the occurrence of self-superparasitism and the rate of escaping to encapsulation of this parasitoid. Knowledge of host-parasitoid immunological interaction is crucial when evaluating the potential of an endoparasitoid as a biological control candidate. Parasitoid-exposed T. absoluta larvae were dissected in vivo under light stereoscope microscope at 24-h intervals, for five days after exposition to detect encapsulation. The preimaginal stages of P. dignus and numbers of healthy and encapsulated immature parasitoids per host were recorded. Samples of parasitoid eggs and larvae were processed for SEM visualization of encapsulation. Necropsies evidenced that only the early first larval instar of P. dignus (up to 96 h-old) was partially or completely encapsulated. A non-melanized capsule, formed by layers of granulocyte-type hemocytes enveloping around the parasitoid body, was recorded. Approximately 50% of the parasitized T. absoluta larvae had significantly only one P. dignus egg, meanwhile supernumerary parasitization yielded up to seven immature parasitoids per host. The proportion of single-early first larval instar of P. dignus reached ô 0.5 and decreased significantly as the number of parasitoid individuals per host increased. P. dignus encapsulation and its ability to overcome with the host immune defense through self-superparasitism indicate that T. absoluta is a semi-permissive host for this parasitoid.